The dynamic changes and influencing factors of visual symptoms after small incision lenticule extraction - Han Chen; Xiuyu Mao; Dongye Xu; Chenwen Guo; Jinhui Dai (BMC Ophthalmology, 2023)
Abstract Background To investigate the dynamic changes and influencing factors of visual symptoms after small incision lenticule extraction (SMILE). Methods This was a prospective observational study. Visual symptoms including glare, haloes, starbursts, hazy vision, fluctuation, blurred vision, double vision and focusing difficulties were evaluated before and 1, 3, 6 months after SMILE using a questionnaire. Generalized linear mixed models were used to assess the effects of preoperative characteristics and objective visual quality parameters on postoperative visual symptoms. Results 73 patients/146 eyes were enrolled. Preoperatively, the most common symptoms were glare (55% of eyes), haloes (48%), starbursts (44%) and blurred vision (37%). At 1 month postoperatively, the incidence and extent scores of glare, haloes, hazy vision and fluctuation rose significantly. At 3 months, the incidence and extent scores of glare, haloes and hazy vision restored to baseline. And at 6 months, the extent scores of fluctuation returned to baseline. Other symptoms (e.g., starbursts) did not change before and 1, 3, 6 months after SMILE. Preoperative visual symptoms were associated with postoperative symptoms, as patients with a symptom preoperatively had higher postoperative scores for that symptom. Age was related to postoperative extent of double vision (coefficient = 0.12, P = 0.046). There were no significant associations between postoperative visual symptoms and preoperative SE, scotopic pupil size, angle kappa (with intraoperative adjustment), postoperative HOAs or scattering indexes. Conclusions The incidence and extent scores of hazy vision, glare, haloes and fluctuation increased at the first month after SMILE, and recovered to baseline at 3 or 6 months. Preoperative visual symptoms were associated with the postoperative symptoms and should be fully considered before SMILE.